Clean and efficient dual-fuel combustion using OMEx as high reactivity fuel: Comparison to diesel-gasoline calibration. (15th July 2020) - Benajes, Jesús; García, Antonio; Monsalve-Serrano, Javier; Sari, Rafael
Highlights: Dual-fuel engine calibrated using diesel-gasoline and OMEx-gasoline pair of fuels. Soot values under the detection limit with OMEx-gasoline for all the engine map. NOx emissions reduced with OMEx by using higher EGR levels without soot penalty. Higher efficiency with OMEx due to lower pumping losses and better combustion control. Abstract: From previous results in a single-cylinder engine platform, it can be concluded that the dual-mode dual-fuel (DMDF) concept can be a potential solution to overcome the major constraints found with other single-fuel low temperature combustion modes. To extend these findings to a real application, this work evaluates the potential of the diesel-gasoline DMDF concept on a multi-cylinder 8L engine in terms of performance and emissions. To do this, a full engine calibration map was obtained following a specific methodology. The emissions results show that diesel-gasoline DMDF allows to achieve EURO VI NOx and soot emissions in a great portion of the engine map. Nonetheless, the levels of these pollutant at high load conditions exceed the EURO VI limits by far due to the need of implementing a diffusive combustion strategy with high EGR levels to avoid excessive in-cylinder pressure gradients. To mitigate this issue, the use of Oxymethylene ether (OMEx) instead of diesel fuel is proposed. A dedicated engine calibration was developed for the OMEx-gasoline DMDF concept following the same methodology. The results show that the oxygen content in the OMEx molecule allows to achieve a fully EUVI compliant engine calibration in terms of NOx with engine-out soot levels lower than 0.01 g/kWh. Moreover, due to the lower stoichiometric air–fuel ratio with this fuel, the air management system requirements are lower, reducing the pumping losses and increasing the brake thermal efficiency in most of the calibration map.